A Man Ahead of His Time: Bill Hannon and the Founding of DMI. (24th March 2020) - Tobin, John
Abstract : "Nothing in my design education had prepared me for the thoroughly foreign culture I found myself in." Bill Hannon Long before "design" became a corporate buzzword, Bill Hannon's early—and difficult—experiences as a design manager led him to create DMI.